Differential Expression of Myofibrillar Proteins during Chilling and Ageing of Chevon Semitendinosus Muscle : doi: 10.5958/2581-6616.2021.00002.5 - Devatkal, Suresh (Journal of Meat Science, 2022)
Conversion of muscle to meat needs carcasses to be chilled for an extended period. During this process, several proteins are broken down into peptides and making meat more tender and palatable. Proteomic tools are employed to study these protein changes during ageing. Therefore, in this work, mass spectrometry was deployed to identify the differential expression of goat semitendinosus muscles proteins. Results revealed a total of 291 proteins of which 103 proteins were differentially expressed between aged and non-aged samples. In aged meat, up-regulated proteins were: myosin light chain/MLC-3 and MLC-1, myosin-I, myosin-II and myosin-III, troponin-C, histone, ATP synthase, cytochrome-C, annexin-A, creatine kinase and tropomyosin alpha chain. This study showed the advantages of ageing in goat meat and indicated probable protein markers associated with meat quality in goat meat.